The effects of psychological defense in the stage of ethnic socialization, and the mechanisms of individuation during subject-act activity - M. Dyduh, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
Psychological defense mechanisms could lead to distortions of ethnic identification – etno-fanatismus, intra-personal conflict, negative stereotyping, etc. An adult person can realize that the problems that have arisen in the socialization process do not contribute to the effective development of the individual and of the act of ethnic individuation to find its own integrity and sense of being. We believe the mechanisms of ethnic individuation are: awareness, appropriation, rethinking, differentiation, internalization, creative implementation, integration.
Keywords: psychological defense; identity; action activity